Drivers of net methane uptake across Greenlandic dry heath tundra landscapes - St Pierre, Kyra A.; Danielsen, Birgitte Kortegaard; Hermesdorf, Lena; D'Imperio, Ludovica; Iversen, Lars Lønsmann; Elberling, Bo (Soil biology & biochemistry, 2019)
Methane (CH4) is a potent greenhouse gas that is naturally produced and consumed in soil. The processes result in that soils may function as either a net sink or source of atmospheric methane. Although dry heath tundra ecosystems have recently been identified as important net sinks of atmospheric CH4, we understand little about how similar dry heath sites compare across both elevational gradients and wider geographical areas with regards to CH4 fluxes. To address this shortcoming, we measured CH4 fluxes and soil characteristics under ambient and experimental warming conditions at low and high elevation sites in South (61°N) and West (69°N) Greenland. We then used a structural equation model to explain CH4 fluxes in relation to air temperatures and soil moisture. Soils across all sites were almost universal net CH4 sinks (range for ambient plots: −1.2 to −3.9 μmol m−2 h−1). Observed soil CH4 fluxes across all sites were significantly positively correlated to soil temperatures at 5 cm depth and negatively correlated to soil moisture. Additional factors such as soil pH and disturbance could also help to explain the differences in CH4 fluxes between similar dry heath sites across greater spatial scales. Understanding the importance of these factors is likely critical to more accurately upscale plot-level measurements of CH4 fluxes in constraining the terrestrial high latitude CH4 sink. •The importance of soil characteristics on CH4 uptake across dry heath ecosystems.•Higher CH4 uptake in West vs. South Greenland despite of higher soil moisture.•CH4 uptake predicted by combination of soil moisture and temperature.•Upscaling across wider landscapes challenged by variability in other soil factors.